Ice cap surface lineaments in the Vostok-Dome C area, East Antarctica. What are they telling us on the East Antarctica craton tectonics? - CIANFARRA, Paola; SALVINI, Francesco (2008)
Since the recent discovery of subglacial lakes beneath the East Antarctic ice cap, the international scientific community have performed extensive geophysical investigations in order to define the poorly known bedrock physiography of the East Antarctic craton. Increasingly available satellite images of remote regions of the globe have provided preliminary constraints for unravelling the tectonic evolution of the East Antarctic plate. Radio echo sounding (RES) data collected in the Vostok-Dome C region revealed the presence of regional, elongated subglacial valleys, namely the Aurora and Concordia trenches (Tabacco et al. 2003). Their marked asymmetric morphology is similar to that of the Vostok lake depression and relates to the activity of two crustal west-dipping listric normal faults of Cenozoic age with a length of over 100 km (Cianfarra et al., 2003). The Radarsat mosaic of Antarctica shows abrupt changes in tones that run across the mosaic and have a length of hundreds to thousands of kilometres. The mosaic therefore reveals for the first time the presence of regional-scale sub-parallel linear features on the ice cap surface expressed on the image mosaic as sharp tonal variations and marked textural anisotropies (see Fig. 1). These intriguing linear features, up to several hundreds of kilometres long and less than 4-5 kilometres wide, will be referred to as lineaments, following Wise (1969) and Wise et al. (1985). This work investigates how the lineament pattern detected on the ice surface relates to the morpho-tectonic setting of the bedrock in the Vostok-Dome C region. Lineaments detected on the Radarsat mosaic of Antarctica and on the ice surface and bedrock morphology DEMs cluster in domains (sensu Wise et al., 1985), similarly to lineaments in emerged regions. Short, well defined lineaments detected on the high-pass spatially filtered Radarsat image depend on the roughness of the bedrock, which is determined by the tectonic setting of the area. Longer lineaments detected on the high-pass spatially ...